2023
DOI: 10.3390/v15020387
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Exposure to Bacteriophage Cocktails against Pseudomonas aeruginosa or Escherichia coli Provokes Marginal Humoral Immunity in Naïve Mice

Abstract: Phage therapy of ventilator-associated pneumonia (VAP) is of great interest due to the rising incidence of multidrug-resistant bacterial pathogens. However, natural or therapy-induced immunity against therapeutic phages remains a potential concern. In this study, we investigated the innate and adaptive immune responses to two different phage cocktails targeting either Pseudomonas aeruginosa or Escherichia coli—two VAP-associated pathogens—in naïve mice without the confounding effects of a bacterial infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Weissfuss et al. studied the immune responses following application of a phage cocktail (comprising DSM 19872/JG005 and DSM 22045/JG024) to naive mice [ 29 ]. The authors were able to show that phages injected intraperitoneally reached the systemic circulation of mice within six hours without inducing an increase of polymorphonuclear neutrophils in the blood.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weissfuss et al. studied the immune responses following application of a phage cocktail (comprising DSM 19872/JG005 and DSM 22045/JG024) to naive mice [ 29 ]. The authors were able to show that phages injected intraperitoneally reached the systemic circulation of mice within six hours without inducing an increase of polymorphonuclear neutrophils in the blood.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, no adverse effects due to phage application could be assessed. In summary, the authors concluded that phage cocktails constitute promising antibacterial treatment options for P. aeruginosa infections in the future [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repetitive dosage of phage cocktails may elicit a humoral response and may result in failure in the clinical trial. 61 Antibody production may be responsible for the failure of outcomes. A naive patient who has not been treated with phage may have pre-existing natural antibodies that resist the phage therapy results compared to a patient who has already undergone phage treatment.…”
Section: Immunogenic Responses During Phage Therapymentioning
confidence: 99%
“…Histopathological analysis shows no elicitation of innate or adaptive immunity but a slight humoral response. Repetitive dosage of phage cocktails may elicit a humoral response and may result in failure in the clinical trial 61 . Antibody production may be responsible for the failure of outcomes.…”
Section: Immunogenic Responses During Phage Therapymentioning
confidence: 99%